Gut mycobiome in cardiometabolic disease progression: current evidence and future directions - Wei, Xiaoyu; Guo, Zixin; Wang, Jingyang; Gao, Dan; Xu, Qiang; Hua, Shengyu (Frontiers in Microbiology, 2025)
Cardiometabolic diseases (CMD) are a cluster of complex syndromes characterized by cardiovascular damage resulting from metabolic dysregulation; however, their underlying mechanisms remain unclear. Recently, CMD research has paid considerable attention to the gut microbiota, though the emphasis has been on bacterial communities, and the gut mycobiome’s role is still not well understood. Hence, this review consolidates information on the correlation between the gut mycobiome and CMD and examines how the gut mycobiome may play a role in CMD progression. Accumulating evidence indicates that gut mycobiome dysbiosis, particularly the aberrant expansion of specific fungal genera such as Candida and Saccharomyces, is closely associated with the development and progression of cardiometabolic diseases. This association is primarily mediated through multiple mechanisms. For instance, fungal metabolites (enzymatic derivatives, alcohol) enhance intestinal lipid absorption, accelerate hepatic steatosis, and trigger systemic insulin resistance. Meanwhile, dysregulated cross-kingdom interactions disrupt intestinal barrier function, leading to endotoxemia and vascular inflammation, thereby promoting atherosclerosis. Additionally, fungal pathogen-associated molecular patterns activate the immune-metabolic axis, resulting in adipose tissue inflammation and glucose dysregulation. These pathways interact synergistically, collectively exacerbating metabolic dysfunction and cardiovascular damage. We also outline strategies targeting the gut mycobiome as a potential therapeutic approach for cardiometabolic diseases. By integrating current state-of-the-art insights, this review provides a critical reference for the development of novel mycobiome-based interventions in cardiometabolic disease management.